2014
DOI: 10.5539/elt.v8n1p189
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Classroom Walls: Edmodo in Saudi Secondary School EFL Instruction, Attitudes and Challenges

Abstract: This paper investigates the prospects of integrating Edmodo into Saudi EFL female secondary school instruction. It concentrates on students' perceptions and challenges regarding Edmodo use and its effect on their attitudes towards EFL learning. The 42 participants were divided into two groups. The experimental group received traditional teaching plus a six-week daily interaction via Edmodo. The control group received traditional teaching only. Findings of the post-treatment questionnaire show that students' pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 14 publications
6
62
0
3
Order By: Relevance
“…These studies have shown a significant effect of integrating technology in teaching English language on students' English proficiency levels and attitudes towards learning English (Al-Shehri, 2011, Al-Okaily, 2013, AlRowais, 2014, Al-Harbi, 2015, Al-Kathiri, 2015Alresheed, Leask, & Raiker, 2015, Al-Harbi & Alshumaimeri, 2016, Al-Otaibi, 2016Al-Zahrani, 2015).…”
Section: The Saudi Teaching Context and Flipped Classroommentioning
confidence: 99%
“…These studies have shown a significant effect of integrating technology in teaching English language on students' English proficiency levels and attitudes towards learning English (Al-Shehri, 2011, Al-Okaily, 2013, AlRowais, 2014, Al-Harbi, 2015, Al-Kathiri, 2015Alresheed, Leask, & Raiker, 2015, Al-Harbi & Alshumaimeri, 2016, Al-Otaibi, 2016Al-Zahrani, 2015).…”
Section: The Saudi Teaching Context and Flipped Classroommentioning
confidence: 99%
“…The result showed that the use of Edmodo in writing was more effective on EFL learners' writing performance participating in this study. Similarly, Al-Khatiri (2015) investigated the prospects of integrating Edmodo into Saudi EFL female secondary school instruction. It concentrated on students' perceptions and challenges regarding Edmodo use and its effect on their attitudes towards EFL learning.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of teaching writing, Edmodo is one of the effective tools. Accordingly, Edmodo is a free and secure learning platform which is free of advertisements, games and other distractions used to provide a simple way for teachers to create and manage online classroom, and enable students to connect with teacher and other students anywhere and anytime (Balasubramanian, Jaykumar, & Fukey 2014;Thongmak, 2013;ShamsAbadi, Ahmadi, & Mehrdad, 2015;Al-Khatiri, 2015). In teaching writing, Edmodo has some advantages as follows: (1) it offers quick access to writing materials and assignments, (2) combined with particular approach or method or technique, Edmodo leads students to have better organization in writing, (3) Edmodo facilitates either teacher to give feedback on students' shared writing, or students to receive feedback on their writing from their peers and the teacher to make it as considerations in revising and editing their writing, and (4) Edmodo makes students more interested in writing (Stroud, 2010;Balasubramanian, Jaykumar, & Fukey, 2014;Purnawarman, Susilawati, & Sundayana, 2016;Shams-Abadi, Ahmadi, & Mehrdad, 2015 The framework depicts that in producing a piece of writing, some processes must be followed by the students.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its similar appearance to Facebook that students are familiar with, it is very easy to apply to classrooms of all subjects. As for the attitude toward the use of Edmodo and motivation in learning, a large number of studies showed positive results [13,14,15,16,17]. …”
mentioning
confidence: 99%